The effect of ostracism on social withdrawal behavior: the mediating role of self-esteem and the moderating role of rejection sensitivity - Lei, Yuju; Li, Mingyue; Lin, Chen; Zhang, Chenshiyuan; Yu, Zhen (Frontiers in Psychology, 2024)
Extant studies have empirically tested the main two behavior responses following ostracism: prosocial or antisocial. Few studies have investigated the relationship between ostracism and social withdrawal. According to the temporal need-threat model and the self-verification theory, the present study aimed to examine the influence mechanism of ostracism on social withdrawal, especially the mediating role of self-esteem and the moderating role of rejection sensitivity. A total of 1,315 Chinese high school students (52.6% female) completed a written questionnaire. Results showed that ostracism was positively correlated with social withdrawal. Ostracism not only directly predicted social withdrawal, but also indirectly affected social withdrawal by threatening adolescents’ self-esteem. High rejection sensitivity may help aggravate adolescents’ self-esteem threaten perceive from ostracism. Adolescents with high rejection sensitivity felt a greater threat to self-esteem when ostracized. Findings suggest a new direction for understanding individuals’ responses to ostracism.